2000
DOI: 10.2165/00007256-200029050-00001
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and the Athlete

Abstract: Alcohol and the athlete have been linked together since ancient times. It continues to be the most commonly consumed drug among the athletic population. Alcohol use carries significant potential adverse effects for both the health and welfare of the individual. It is suggested that alcohol related problems may be more prevalent in the athletic population due to their risk taking mentality and the age profile of athletes (18- to 24-year-old males). Alcohol consumption also appears to have a causative effect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 13 publications
3
75
0
5
Order By: Relevance
“…For this population, it has been suggested that alcohol consumption is more dependent on social influence than coping 20 . When excessive, alcohol consumption may have a negative influence on health, frequently resulting in disease 21 and injury 22 . However, given the weekly training frequency of the athletes in the present study, the effects of alcohol consumption on the self-reported QoL remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…For this population, it has been suggested that alcohol consumption is more dependent on social influence than coping 20 . When excessive, alcohol consumption may have a negative influence on health, frequently resulting in disease 21 and injury 22 . However, given the weekly training frequency of the athletes in the present study, the effects of alcohol consumption on the self-reported QoL remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Workers with an alcohol hangover reported significantly more conflicts with supervisors and co-workers, and felt miserable or fell asleep on the job (Ames et al, 1997). Also, physical performance of healthy volunteers (Karvinen et al, 1962) and athletes (O'Brien and Lyons, 2000) is significantly reduced during hangover. Binge drinking is especially prevalent among college students.…”
Section: Introductionmentioning
confidence: 99%
“…The NCAA (2006) conducted a survey from 1993 to 2005 and found significant differences in alcohol consumption across a variety of men's and women's sports. Additional researchers have found similar results (e.g., Brenner & Swanwik, 2007;Martens, Watson, & Beck, 2006;O'Brien & Lyons, 2000). The finding that alcohol consumption varies across sport type emphasizes the need to further investigate the role of sport type in alcohol consumption among college athletes.…”
Section: Sport Typementioning
confidence: 64%
“…Sport type refers to the sport that one currently participates in (basketball, football, soccer, etc.). The sport the individual participates in plays a key role in self-concept, because different sport teams have different social norms, which influence the identity and schema of the group's members (O'Brien & Lyons, 2000).…”
Section: Sport Typementioning
confidence: 99%